A representatividade da mulher na trajetória política estadual em Mato Grosso no período de 1946 a 2018 - Campos, Dejenana Keila Oliveira (2023)
This research aims to investigate female under-representation in politics, as well as to analyze the participation and representativeness of women candidates elected in the Mato Grosso political scenario. We focus on the investigation of state deputies elected between 1946 and 2018. The proposal is to understand the political trajectory of these women and the path taken to gain space in the political environment of the state. For this purpose, we dialogue with the feminist movement and gender relations from an anti-racist and decolonial perspective, also relating to other areas of knowledge, in order to better perceive the maintenance of a subaltern position that reduces the representation of women in power. Thus, the justification of the research lies in the fact that historically women have always been underrepresented, which we also see repeating in the political arena, and therefore it becomes necessary to comprehend how their insertion occurs in this space of power. As for the methodological procedures, a bibliographic study and a field study were carried out through: interviews and testimonials with state deputies; documentary analysis of the Instituto Memória do Poder Legislativo of the Legislative Assembly of Mato Grosso; and electoral data from the Superior Electoral Court. The results indicate that state deputies mostly seek to respond to public policies of interest to women, in addition to occupying spaces in politics considered as male, although, in general, the parties lack commitment to the fulfillment of gender quotas.